2015
DOI: 10.1128/aac.01490-15
|View full text |Cite
|
Sign up to set email alerts
|

HIV Drug Resistance Testing by High-Multiplex “Wide” Sequencing on the MiSeq Instrument

Abstract: f Limited access to HIV drug resistance testing in low-and middle-income countries impedes clinical decision-making at the individual patient level. An efficient protocol to address this issue must be established to minimize negative therapeutic outcomes for HIV-1-infected individuals in such settings. This is an observational study to ascertain the potential of newer genomic sequencing platforms, such as the Illumina MiSeq instrument, to provide accurate HIV drug resistance genotypes for hundreds of samples s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 44 publications
2
47
0
Order By: Relevance
“…However, our results also suggest that an average MiSeq coverage depth of 10–100 can still very accurately predict Sanger subtyping results across all genomic regions in these Ugandan non-subtype B HIV samples. This agrees with previous observations that MiSeq can accurately predict Sanger-derived rt sequences at coverage depth below 100 [23]. Furthermore, we showed that MiSeq was more successful in yielding full-length GP120 sequences compared to Sanger sequencing, supporting the move to deep sequencing in HIV env genetic studies.…”
Section: Discussionsupporting
confidence: 91%
“…However, our results also suggest that an average MiSeq coverage depth of 10–100 can still very accurately predict Sanger subtyping results across all genomic regions in these Ugandan non-subtype B HIV samples. This agrees with previous observations that MiSeq can accurately predict Sanger-derived rt sequences at coverage depth below 100 [23]. Furthermore, we showed that MiSeq was more successful in yielding full-length GP120 sequences compared to Sanger sequencing, supporting the move to deep sequencing in HIV env genetic studies.…”
Section: Discussionsupporting
confidence: 91%
“…In NGS deep sequencing the depth of coverage refers to the number of viral variants sequenced, typically several hundred. Researchers have shown that harnessing the cost savings of NGS using a “wide sequencing” strategy, wherein many samples are processed in a single run with a lesser depth of coverage, could be a viable method of genotypic testing in LMICs (Dudley et al, 2012; Lapointe et al, 2015). Cost-effectiveness models using NGS platforms have not been published, but the estimated cost per sample is much lower than SGRT at 1 to 20 USD (Dudley et al, 2012; Lapointe et al, 2015).…”
Section: Hiv-1 Drug Resistance Testingmentioning
confidence: 99%
“…These variants are usually present as minority members of the virus population, which can be selected to dominate over drugsusceptible variants under drug pressure (25)(26)(27). For this reason, a series of ultrasensitive HIV-1-genotyping assays, based on deep sequencing (next-generation sequencing [NGS]), have been developed to detect drug-resistant HIV-1 variants at levels below 20% of the viral population in an infected individual (24,(28)(29)(30)(31). Several studies have associated early detection of these minority HIV-1 drug-resistant variants with subsequent treatment failure (32)(33)(34)(35)(36)(37); however, with the advent of single-pill once-a-day (QD) cART regimens, treatment failures in HICs are rare, and the relevance of minority members of the viral population to the ART outcome is still under debate (32,(38)(39)(40)(41).…”
mentioning
confidence: 99%